Green synthesis of titanium dioxide photocatalyst using Lactobacillus bulgaricus for processing palm oil mill effluent - L. Agustina; M. Romli; P. Suryadarma; S. Suprihatin (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: To improve photocatalytic degradation perfomance, photocatalyst particles with a larger surface area preferred. The effectiveness of titanium dioxide as a photocatalyst depends on the synthesis method used. The method affect the particle size, crystallinity and phase composition of the produced catalyst. This study aims to develop a green synthesis process of nano- titanium dioxide photocatalysts for the advanced treatment of palm oil mill effluent.METHODS: The green synthesis of titanium dioxide nanoparticles used de Man-Rogosa-Sharpe broth media containing Lactobacillus bulgaricus culture and titanium oxyhydroxide metal oxide. The factors investigated were the molarity of titanium oxyhydroxide (0.025 molar; 0.035 molar and 0.045 molar) and temperature (40; 50 and 60 degrees Celsius). The synthesized photocatalyst was characterized using a particle size analyzer to determine the particle size. The produced photocatalyst with a nanoparticle size range of 1-100 nanometer was further characterized using scanning electron microscopy-energy dispersive X-ray and X-ray diffraction. The photocatalyst was tested for advanced treatment of palm oil mill secondary effluent. The factors investigated in this test included the irradiation time and titanium dioxide photocatalyst dosage. The treatment performance was evaluated in terms of effluent quality and pollutant elimination efficiency.FINDINGS: Nano titanium dioxide photocatalysts have been synthesized through titanium oxyhydroxide metal oxide biologically using Lactobacillus bulgaricus. The synthesis process at a temperature of 60 degrees Celsius and a 0.025 molar metal oxide solution produced a titanium dioxide photocatalyst with a size of 33.28 nanometer. The content of titanium and oxygen constituents in the photocatalyst was confirmed to be 39.06 percent and 47.95 percent respectively, with 67.6 percent titanium dioxide crystallinity in a theta degree of 25.4. This indicates that the green synthesis has produced an anatase diffraction nano titanium dioxide photocatalyst. Testing the titanium dioxide photocatalyst to treat palm oil mill secondary effluent yielded in elimination efficiency of 16.16-27.27 percent for chemical oxygen demand and 11.05-21.95 percent for biological oxygen demand. Phenol, which is toxic and difficult to degrade biologically, could eliminated significantly (up to 81.12 percent) using a photocatalyst dose of 1 gram per liter at a time irradiation of 2.5 hour.CONCLUSION: The biological synthesis of nano titanium dioxide photocatalysts is affected by temperatures and metal oxide concentrations. The photocatalytic process for advanced treatment of palm oil mill secondary effluent shows that this synthesis process effectively eliminates phenols. Some compounds such as lignin, amino acids, and pectin are not significantly mineralized using this process.